2006
DOI: 10.1149/1.2183927
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Intermediate-Temperature Fuel Cell Using a Proton-Conducting Sn[sub 0.9]In[sub 0.1]P[sub 2]O[sub 7] Electrolyte

Abstract: Performance of a fuel cell using Sn 0.9 In 0.1 P 2 O 7 as the electrolyte was evaluated in the temperature range of 150-300°C under unhumidified conditions. The IR drop and electrode overpotential of the cell were measured separately by the current interruption method. The dc conductivity values of the electrolyte between 150 and 300°C, estimated from the IR drop, were comparable to the ac conductivity values ͑1.48 ϫ 10 −1 -1.95 ϫ 10 −1 S cm −1 ͒ of the electrolyte. The cell performance was improved by forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…We have recently reported that 10 mol % In 3+ -doped SnP 2 O 7 (Sn 0.9 In 0.1 P 2 O 7 ) shows high proton conductivities of above 10 À1 S cm À1 between 100 and 350 8C under water-free conditions. [13] This material has also been used as an electrolyte in fuel cells, [14] and herein we report the selective oxidation of methane to methanol in a hydrogen-oxygen fuel cell containing Sn 0.9 In 0.1 P 2 O 7 as electrolyte.…”
mentioning
confidence: 86%
“…We have recently reported that 10 mol % In 3+ -doped SnP 2 O 7 (Sn 0.9 In 0.1 P 2 O 7 ) shows high proton conductivities of above 10 À1 S cm À1 between 100 and 350 8C under water-free conditions. [13] This material has also been used as an electrolyte in fuel cells, [14] and herein we report the selective oxidation of methane to methanol in a hydrogen-oxygen fuel cell containing Sn 0.9 In 0.1 P 2 O 7 as electrolyte.…”
mentioning
confidence: 86%
“…Firstly, the ohmic resistance was strongly dependent on the operation temperature, which reflects the large proton conductivity dependence of the electrolyte on the temperature. 46,47 Secondly, the charge-transfer resistance was reduced by an increase in the temperature, which is ascribed to the enhanced kinetics of both the redox reaction at the anode and the ORR/OER at the cathode at elevated temperatures. Thirdly, the sharp rise in the low frequency range was not parallel to the imaginary axis, which indicates that these electrodes do not function as simple EDL electrodes.…”
Section: +mentioning
confidence: 99%
“…A fuel cell using the thin Sn0.9In0.1P2O7 electrolyte membrane yielded the best power density of 264 mW・cm -2 under unhumidified hydrogen/air conditions 23) . Moreover, an attempt to apply these materials as ionomers for the cathode at intermediate temperatures was also made 29), 30) .…”
Section: )~28)mentioning
confidence: 99%
“…However, these power density values are much lower compared to those expected from the ohmic resistances (as an example, 0.24 Ω・cm 2 at 200℃) of the electrolyte, which could be ascribed to the large polarization resistance of the Pt/C cathode used. One of the main reasons for the poor ORR activity is thought to be the lack of proton conduction in the catalyst layer 12), 23) . The ORR occurs at the three-phase bound ary (TPB) (gas-phase/electrode/electrolyte) where all electrons, protons, and gases are available.…”
Section: Use Of Sn09in01p2o7 As Ionomers For Cathode Inmentioning
confidence: 99%
See 1 more Smart Citation